New Paradigms Within the Communication Sciences - Başar, Enes Emre (Cambridge Scholars Publisher, 2021)
This collection of essays emphasizes new and emerging research paradigms in the communication world. It provides researchers and practitioners with new paradigms in the form of ideas, concepts, trends, values and practices in the communication realm. In addition, the contributions here examine current, emerging, and cutting-edge approaches to communication in the broadest sense. The focus of this book is to provide an in-depth understanding of the phenomenon of continuous and rapid growth of new communication means, shifting from the traditional unidirectional sharing of information to multidi.